The Second Machine Age Work, Progress, and Prosperity in a Time of Brilliant Technologies - Brynjolfsson, Erik; McAfee, Andrew (Tantor Audio, 2025)
A New York Times bestseller. A "fascinating" (Thomas L. Friedman, New York Times) look at how digital technology is transforming our work and our lives. In The Second Machine Age MIT's Erik Brynjolfsson and Andrew McAfee--two thinkers at the forefront of their field--reveal the forces driving the reinvention of our lives and our economy. As the full impact of digital technologies is felt, we will realize immense bounty in the form of dazzling personal technology, advanced infrastructure, and near-boundless access to the cultural items that enrich our lives. Amid this bounty will also be wrenching change. Professions of all kinds--from lawyers to truck drivers--will be forever upended. Companies will be forced to transform or die. Recent economic indicators reflect this shift: fewer people are working, and wages are falling even as productivity and profits soar. Drawing on years of research and up-to-the-minute trends, Brynjolfsson and McAfee identify the best strategies for survival and offer a new path to prosperity. These include revamping education so that it prepares people for the next economy instead of the last one, designing new collaborations that pair brute processing power with human ingenuity, and embracing policies that make sense in a radically transformed landscape.
Audio book. - Online resource; title from title details screen (cloudLibrary, viewed March 19, 2025)
Keywords: Information technology -- Economic aspects; Economic development -- Technological innovations; Progress -- Social aspects; Social stratification; Technologie de l'information; Aspect économique; Développement économique; Innovations; Progrès; Aspect social; Stratification sociale; social stratification; Industries; Internet; COMPUTERS; Electronics; TECHNOLOGY & ENGINEERING; BUSINESS & ECONOMICS; Audiobooks; Livres audio